2021
DOI: 10.3390/plants10091790
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal Inoculation Enhances the Salt Tolerance of Quercus mongolica Seedlings

Abstract: Salt stress harms the growth and development of plants, and the degree of soil salinization in North China is becoming increasingly severe. Ectomycorrhiza (ECM) is a symbiotic system formed by fungi and plants that can improve the growth and salt tolerance of plants. No studies to date have examined the salt tolerance of Quercus mongolica, a typical ectomycorrhizal tree species of temperate forests in the northern hemisphere. Here, we inoculated Q. mongolica with two ectomycorrhizal fungi (Gomphidius viscidus;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The antioxidant enzymes mainly include peroxidase (POD), superoxide dismutase (SOD), ascorbate oxidase (APX) and catalase (CAT), and the nonenzymatic antioxidant substances mainly include reduced glutathione (GSH), reduced ascorbic acid (AsA) and carotenoids [ 9 ]. Many studies have shown that the responses of different protective enzymes to drought stress vary [ 10 , 11 , 12 ]. The protective enzymes that play a dominant role in plants may also differ between periods of stress [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant enzymes mainly include peroxidase (POD), superoxide dismutase (SOD), ascorbate oxidase (APX) and catalase (CAT), and the nonenzymatic antioxidant substances mainly include reduced glutathione (GSH), reduced ascorbic acid (AsA) and carotenoids [ 9 ]. Many studies have shown that the responses of different protective enzymes to drought stress vary [ 10 , 11 , 12 ]. The protective enzymes that play a dominant role in plants may also differ between periods of stress [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, B. pendula colonisation was stronger than for S. alba (15%) and S. caprea (9%), which may indicate high tolerance of silver birch to environmental stresses. Moreover, as observed by Bai et al 56 in the case of Q. mongolica seedlings, ectomycorrhizal inoculation can improve salt tolerance. Zwiazek et al 57 , examining pine seedlings exposed to NaCl, also found reduced Na accumulation and higher growth rates in the case of seedlings inoculated with urban soil containing specific fungi genera.…”
Section: Discussionmentioning
confidence: 63%
“…reported the physiological mechanisms of exogenous ABA regulation of drought stress in ginger, observed increased activities of SOD, POD, and CAT in plant leaves upon early application of ABA to the roots. In our study, POD activity in S. salsa initially decreased insigni cantly and then increased with the increasing severity of drought stress, which may be because different antioxidant enzymes have different responses to drought stress(Anjum et al 2011;Bai et al 2021). Protective enzymes that play a dominant role in plants may also differ under stress(Seki et al 2007).…”
mentioning
confidence: 50%